Revised Seventh Five Year Plan 1985-'90 Sector: Introduction Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1985)
Lakshadweep is the smallest Union Territory with a land area of only 32 sq. kms. and a population (1981) of 40,249. Formerly part of the then Madras State, it became a Union Territory in 1956 and planned development may really be stated to have started only then.
Planning Department, Secretariat, Lakshadweep, Kavaratti